PEMIKIRAN PAHAM KOMUNIS PERSPEKTIF PANCASILA - Casedi, Edi; Hidayat, Syamsul (Universitas Muhammadiyah Surakarta, 2017)
Pancasila is the foundation of the Republic of Indonesia were scattered on God, just and civilized humanity, unity of Indonesia, Democracy and led by the wisdom of wisdom in deliberation representation, social justice for all Indonesian people. Belief in God Almighty be a fundamental principle of the five precepts that exist. This precept demands that citizens of the Republic of Indonesia for the godless. However, in reality happened in the history of Indonesia and recognition Indonesian communist party in the election. This study tried to sit communism in the ideology of Pancasila and whether he has a space in it. This research is to answer the question in the hope that people understand and be aware of the teachings of communism when seated on the basis of the Homeland. Be a kind of literary qualitative research with historical and philosophical approach. Results showed communism research from the aspect of ideology, politics, socio-economics is contrary to the principles of Pancasila which are the foundation of the Republic of Indonesia. Thus, by reason of the above teachings and ideology of communism do not have space in Pancasila. Because something in violation not possible to put together and aligned. Because ideology is contradictory and do not have space in the basic state and the nation of Indonesia, should and rightly where this doctrine is not worth living fertile motherland ever betrayed by the PKI to perform a coup over the legitimate government with efforts to make Indonesia not sovereign to make